Artificial Intelligence and Digital Humanities in the 21st Century - Adekoya, Samuel Olamide; Segun, Adediran idowu; Dairo , Afolorunso Oalekan (Corpus Intellectual, 2025)
This study examines how AI is transforming methodologies and ethical considerations in Digital Humanities in the 21st century, a field that combines traditional humanities scholarship with digital technologies. While AI offers new opportunities for analysing cultural artifacts and texts, it also raises concerns about the dehumanisation of scholarly work, bias in algorithms, and the erosion of critical, humancentered analysis. Using the framework of Technological Determinism, this research explores both the opportunities and challenges AI presents in the Digital Humanities. This study uses a mixed-methods approach, incorporating historical analysis, phenomenological inquiry, and content analysis to examine AI's influence on Digital Humanities. While AI enhances data analysis and access to knowledge, it also presents ethical concerns related to bias, privacy, and the protection of humanistic values in research. The study proposes five key recommendations: fostering collaboration between computer science and humanities scholars, providing training for researchers, encouraging ethical discussions around AI, investing in AI tools tailored for the humanities, and promoting accessible AI resources in education. It highlights the importance of balancing technological advancements with the preservation of traditional academic values in Digital Humanities.